Cryoablation for locally advanced clinical stage T3 prostate cancer: a report from the Cryo‐On‐Line Database (COLD) Registry. (22nd January 2014) - Ward, John F.; DiBlasio, Christopher J.; Williams, Christopher; Given, Robert; Jones, J. Stephen
Abstract : Objective: To assess the oncological and functional outcomes of primary prostate cryoablation for men with clinical stage T3 (cT3) prostate cancer, as although radical prostatectomy (RP) or external beam radiotherapy (EBRT) are the standard treatments for locally advanced cT3 prostate cancer some patients opt for nonextirpative prostate cryoablation instead. Patients and Methods: The Cryo‐On‐Line Database (COLD) Registry was queried to identify patients with cT3 prostate cancer treated with whole‐gland cryoablation (366 patients). We assessed biochemical disease‐free survival (bDFS) using the Phoenix definition and determined reported rates of urinary incontinence and retention, sexual activity, and rectourethral fistulisation after treatment. Patients were subsequently assessed according to whether they were administered neoadjuvant androgen‐deprivation therapy or not (ADT; 115 patients, 31.4%). Results: For the entire cohort, the 36‐ and 60‐month bDFS rates were 65.3% and 51.9%, respectively. Patients who received neoadjuvant ADT had statistically nonsignificantly higher 36‐ and 60‐month bDFS rates (68.0% and 55.4%, respectively) than patients who did not receive neoadjuvant ADT (55.3% and 36.9%, respectively). The after treatment urinary incontinence rate was 2.6%; urinary retention rate, 6.0%; sexual activity rate, 30.4%; and rectourethral fistulisation rate, 1.1%. Conclusions: Cryoablation for patients with cT3 prostate cancer leads to less favourable bDFS than that after RP or RT for the same group of men. The after treatment rectourethral fistulisation rates for patients with cT3 disease are higher than in those with organ‐confined prostate cancer treated with cryoablation; however, urinary dysfunction and sexual activity rates are similar for men with cT3 to those reported from this same registry in men with cT2 disease. The addition of neoadjuvant ADT (though not studied prospectively here) should be strongly considered if a patient with cT3 prostate cancer is to be treated with cryoablation.